2011
DOI: 10.5120/2962-3946
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Power Dissipation in Logic Circuits

Abstract: The most research on the power consumption of circuits has been concentrated on the switching power and the power dissipated by the leakage current has been relatively minor area. In today"s IC design, one of the key challenges is the increase in power dissipation of the circuit which in turn shortens the service time of battery-powered electronics, reduces the longterm reliability of circuits due to temperature-induced accelerated device and interconnects aging processes, and increases the cooling and packagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A few techniques were proposed and discussed in the literature to curtail static power such as stack approach, sleep transistor approach, sleepy stack approach and zigzag approach. Each low power technique has its own merits and demerits [17].…”
Section: ░ 2 Existing Workmentioning
confidence: 99%
“…A few techniques were proposed and discussed in the literature to curtail static power such as stack approach, sleep transistor approach, sleepy stack approach and zigzag approach. Each low power technique has its own merits and demerits [17].…”
Section: ░ 2 Existing Workmentioning
confidence: 99%
“…For a new technology, where 18% gate oxide thickness (t ox ) is reduced, the minimum thickness for reliable operation is 2 nm, but at 65 nm it is 1.4 nm. Hence the gate leakage is 1000 times more than the sub-threshold leakage [2]. To utilize the scaling benefits with minimum SCEs the device structures are continuously being tried to be modified.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover thinner gate oxides have also caused increase in gate leakage current [1]. Recent research has shown that the sub threshold leakage current is more prominent than the dynamic current in the overall power dissipation [2] [3]. Reduction of sub threshold leakage power is highly desirable for battery operated portable systems, which remain in the standby state for the majority of their operating time.…”
Section: Introductionmentioning
confidence: 99%